Microscopic characteristics, chemical compositions and bioactivities of Alpinia vietnamica - Nguyen, Dinh Quynh Phu; Nguyen, Hoai Bao Chau; Doan, Quoc Tuan; Nguyen, Khanh Thuy Linh; Tran, Van Nguyen; Le, Thi Khanh Linh (Tạp chí Y Dược Huế, 2023)
Background: The genus Alpinia is one of the diverse genera in Thua Thien Hue province, in which many species have been used as medicine. But until now, studies on A. vietnamica have rarely been reported. Objectives: The present study was aimed at the determination of microscopic characteristics and chemical compositions as well as evaluating the antioxidant and acetylcholinesterase inhibitory activities of A. vietnamica. Materials and methods: A. vietnamica was collected in Phong Dien district, Thua Thien Hue province. Anatomic structures and powder properties were determined by the microscopic method. Phytochemical screening was conducted by specific chemical reactions. The Folin-Ciocalteau method and the aluminum chloride-flavonoid assay, respectively, were used to quantify the total polyphenol (TPC) and total flavonoid contents (TFC). Antioxidant activity was assessed using the DPPH assay, while acetylcholinesterase (AChE) inhibitory activity was evaluated using the Ellman method. Results: The microscopic characteristics of this species have been described. Phytochemical analysis results revealed the presence of flavonoids, coumarins, and tannins in A. vietnamica. The ethanol extract from the aerial part of A. vietnamica had higher polyphenol and flavonoid contents than the underground part extract. Moreover, this extract also displayed a stronger DPPH radical scavenging and exhibited AChE inhibitory activities. Conclusion: This is the first report on the microscopic characteristics, chemical compositions, and biological activities of A. vietnamica